2012
DOI: 10.30972/vet.2311802
|View full text |Cite
|
Sign up to set email alerts
|

Listeriosis en bovinos de la Provincia de Buenos Aires, Argentina

Abstract: <p>Se reali­zó un estudio retrospectivo de casos de listeriosis bovina ocurridos en diferentes partidos de Provincia de Buenos Aires (Argentina). Se utilizaron las técnicas diagnósticas de histopato­logía, bacteriología e inmunohistoquímica. De 17 casos confirmados por esta última técnica, en 7 de ellos se dispuso de material para el cultivo bacteriológico y solo en 3 casos se pudo aislar <em>Listeria monocytogenes. </em>El 64,7% de los casos de listeriosis se presentaron en rodeos que consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
3
2
2
Order By: Relevance
“…However, only one of the animals tested positive by IHC. This finding differs from those reported in other studies conducted with cattle and small ruminants (Rissi et al 2006, Oevermann et al 2010, Margineda et al 2012, which showed positive results by IHC in all of the animals analyzed. Nevertheless, differences in IHC staining have been observed in cases of listeriosis in goats, ranging from strong to absent, depending on the time of lesion evolution (Rissi et al 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, only one of the animals tested positive by IHC. This finding differs from those reported in other studies conducted with cattle and small ruminants (Rissi et al 2006, Oevermann et al 2010, Margineda et al 2012, which showed positive results by IHC in all of the animals analyzed. Nevertheless, differences in IHC staining have been observed in cases of listeriosis in goats, ranging from strong to absent, depending on the time of lesion evolution (Rissi et al 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the disease affected calves aged <40 days. The main clinical signs observed by the veterinarian were ataxia, limb paralysis, lateral recumbency, and death, similar to those described for cattle (Margineda et al 2012) and small ruminants (Rissi et al 2006(Rissi et al , 2010. Morbidity (6.38%) and lethality (100%) were also similar to those described for these species.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…in Uruguay is rare. A similar situation might occur in the region, because in Argentina there are few reports (Margineda et al, 2012;Alvarez et al, 2018), while in Brazil no similar situation has been described.…”
Section: Discussionmentioning
confidence: 76%